Career Readiness of High School Students: A Comparative Study From A Gender Perspective - Kumara, Agus Ria; Wiyono, Bambang Budi; Atmoko, Adi; Hambali, IM. (Psikopedagogia, 2024)
This study examines the differences in career readiness between male and female students at the high school level, with a focus on cognitive strategies, knowledge of career content, and contextual skills and awareness.  This study uses a quantitative method with a survey design and involves 300 high school students in D.I. Yogyakarta who are selected through convenience sampling techniques. Data were collected using the Conley theory-based Career Readiness Scale, which has been tested with the RASCH model, and analyzed using descriptive statistics. The results of the analysis show that female students have higher career readiness than male students. Significant differences were found in cognitive strategy, knowledge of career content, and contextual skills and awareness, while there were no meaningful differences in academic behavior. These findings underscore the importance of a gender-tailored approach to career guidance and counseling services in schools.